The Role of Digital Public Relations in Reputation Management on Instagram as Applied to Charitable Societies in the Kingdom of Bahrain - Layla Abdarasool Hussein Aldarazi (International Journal of Computers and Informatics, 2025)
The current study examines the role of digital public relations in reputation management via Instagram, applying it to charitable organizations in the Kingdom of Bahrain, and the effectiveness of Instagram in improving their public image. It aims to identify the nature of digital media and its impact on promoting cultural exchange and dialogue in the Kingdom of Bahrain. A survey approach was used, and the available sample, consisting of (80) individuals from Bahraini society, was selected. (26) Males and (45) females were selected through questionnaire analysis and interviews. The study reached several conclusions, the most important of which is that digital public relations has a positive impact on managing the reputation of charitable organizations via Instagram. It also recommended the need to pay attention to the importance of digital public relations, develop clear digital public relations strategies, and attempt to implement them on the ground to achieve the desired goals.